Association Between Vaso-Occlusive Crises and Opioid Prescriptions Among Patients with Sickle Cell Disease: A Retrospective Claims-Based Study - Hyeun Ah Kang; Jamie C. Barner; Kristin M. Richards; Menaka Bhor; Jincy Paulose; Abdullah Kutlar (Journal of Health Economics and Outcomes Research)
**Background/Objectives:** Among sickle cell disease (SCD) patients, vaso-occlusive crises (VOCs) are recurrent and unpredictable attacks of acute pain. These pain crises are often treated with analgesics, including opioids, which have been associated with misuse and overdose. The aim of this study was to examine the association between VOC events and opioid use and assess the association between opioid prescriptions and health care resource utilization among SCD patients.